Grain engineering for efficient near-infrared perovskite light-emitting diodes - Sung-Doo Baek; Wenhao Shao; Weijie Feng; Yuanhao Tang; Yoon Ho Lee; James Loy; William B. Gunnarsson; Hanjun Yang; Yuchen Zhang; M. Bilal Faheem; Poojan Indrajeet Kaswekar; Harindi R. Atapattu; et al. (Nature Communications)
Abstract Metal halide perovskites show promise for next-generation light-emitting diodes, particularly in the near-infrared range, where they outperform organic and quantum-dot counterparts. However, they still fall short of costly III-V semiconductor devices, which achieve external quantum efficiencies above 30% with high brightness. Among several factors, controlling grain growth and nanoscale morphology is crucial for further enhancing device performance. This study presents a grain engineering methodology that combines solvent engineering and heterostructure construction to improve light outcoupling efficiency and defect passivation. Solvent engineering enables precise control over grain size and distribution, increasing light outcoupling to ~40%. Constructing 2D/3D heterostructures with a conjugated cation reduces defect densities and accelerates radiative recombination. The resulting near-infrared perovskite light-emitting diodes achieve a peak external quantum efficiency of 31.4% and demonstrate a maximum brightness of 929 W sr−1 m−2. These findings indicate that perovskite light-emitting diodes have potential as cost-effective, high-performance near-infrared light sources for practical applications.